2022
DOI: 10.3390/app12031678
|View full text |Cite
|
Sign up to set email alerts
|

Virtual and Traditional Lecturing Technique Impact on Dental Education

Abstract: This study tries to identify the influence of the new coronavirus pandemic on dental education by assessing dental students’ perception and their didactic performance regarding virtual and traditional lectures. The final academic performances of students from different years of study at the Faculty of Dental Medicine who participated in undergraduate courses through two different lecturing modes (traditional and virtual) were compared. The same students were evaluated in terms of their preference between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…8 Altogether, videos should be a complement, rather than a competitor to live lectures, particularly as the need for remote education grows, spurred by the COVID-19 pandemic. [3][4][5][6] Viewer survey findings indicated that students are more likely to use online videos as adjunctive study materials than textbooks, social media and journals, consistent with other studies where dental students achieved higher test scores following videos compared to textbook reading (Figure 2). 10,33 MD viewers have grown from 18 to more than 200,000 over the past 6 years, suggesting demand for accessible online resources.…”
Section: Recommendationssupporting
confidence: 87%
See 4 more Smart Citations
“…8 Altogether, videos should be a complement, rather than a competitor to live lectures, particularly as the need for remote education grows, spurred by the COVID-19 pandemic. [3][4][5][6] Viewer survey findings indicated that students are more likely to use online videos as adjunctive study materials than textbooks, social media and journals, consistent with other studies where dental students achieved higher test scores following videos compared to textbook reading (Figure 2). 10,33 MD viewers have grown from 18 to more than 200,000 over the past 6 years, suggesting demand for accessible online resources.…”
Section: Recommendationssupporting
confidence: 87%
“…Videos are also more expensive and time‐consuming to produce initially yet can be repeated year‐after‐year and ultimately result in cost savings 8 . Altogether, videos should be a complement, rather than a competitor to live lectures, particularly as the need for remote education grows, spurred by the COVID‐19 pandemic 3–6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations